Flujograma para la construcción de perfiles geológicos a través del procesamiento de información geográficamente referenciada de tipo vectorial o ráster mediante software para sistemas de información geográfica (SIG) y software de diseño asistido (DAC) (2021)
This document contains the procedure for developing a flow chart on the creation of a geological cross section using QGIS and AutoCAD as tools. This construction was carried out based on the knowledge learned in geology classes, that were subsequently taught to the students during the development of the monitoring sessions. In addition, a bibliographic review of scientific documents and articles was carried out, whose objective was the identification of reference protocols for the flow chart construction.